(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
In conservation and environmental sustainability policies and programs around the world, local environmental stewardship has received more attention and funding. However, environmental stewardship has not gotten enough conceptual focus. Our capacity to comprehend the elements that contribute to environmental stewardship’s success or failure in various contexts and the best ways to assist and facilitate local initiatives may be improved by establishing a precise definition and thorough analytical framework. Here, we provide such a definition and framework. We first define local environmental stewardship as the actions taken by individuals, groups, or networks of actors with a range of objectives and capacities to preserve, care for, or responsibly use the environment in order to achieve environmental and/or social outcomes in a variety of social-ecological contexts. Following a study of the literature on governance, management, and environmental stewardship, we dissect this definition’s elements to produce an analytical framework that can facilitate local environmental stewardship research. Finally, we discuss how the framework could be used to guide descriptive, evaluative, prescriptive, or systematic research on environmental stewardship, as well as potential initiatives and leverage points to promote or assist local stewardship. Further application of this framework in diverse environmental and social contexts is recommended in order to refine the elements and offer insights that will guide and improve the outcomes of environmental stewardship initiatives and investments. Our ultimate objective is to raise awareness of environmental sustainability through stewardship, as a practical and all-encompassing concept for guiding durable and comprehensive idea for directing long-lasting and fruitful...